(untitled) (Swiss Medical Weekly, 2017)
AIM OF THE STUDY Maximal exercise testing may be difficult to perform in clinical practice, especially in obese children who have low cardiorespiratory fitness and exercise tolerance. We aimed to elaborate a model predicting peak oxygen consumption (VO2) in lean and obese children with use of the submaximal Chester step test. METHODS We performed a maximal step test, which consisted of 2-minute stages with increasing intensity to exhaustion, in 169 lean and obese children (age range: 7–16 years). VO2 was measured with indirect calorimetry. A statistical Tobit model was used to predict VO2 from age, gender, body mass index (BMI) z-score and intensity levels. Estimated VO2peak was then determined from the heart rate-VO2 linear relationship extrapolated to maximal heart rate (220 minus age, in beats.min˗1). RESULTS VO2 (ml/kg/min) can be predicted using the following equation: VO2 = 22.82 ˗ [0.68*BMI z-score] ˗ [0.46*age (years)] ˗ [0.93*gender (male = 0; female = 1)] + [4.07*intensity level (stage 1, 2, 3 etc.)] ˗ [0.24*BMI z-score *intensity level] ˗ [0.34*gender*intensity level]. VO2 was lower in participants with high BMI z-scores and in female subjects. CONCLUSION The Chester step test can assess cardiorespiratory fitness in lean and obese children in clinical settings. Our adapted equation allows the Chester step test to be used to estimate peak aerobic capacity in children.